Unresectable Hepatocellular Carcinoma: Transcatheter Arterial Chemoembolization Combined With Microwave Ablation vs. Combined With Cryoablation - Wei, Jialiang; Cui, Wei; Fan, Wenzhe; Wang, Yu; Li, Jiaping (Frontiers in Oncology, 2020)
Background: Transcatheter arterial chemoembolization (TACE) combined with ablation has been widely used for treating unresectable hepatocellular carcinoma (HCC). However, the technique with which TACE should be combined for it to be more effective remains unknown. Purpose: To retrospectively evaluate the efficacy and safety of TACE combined with microwave ablation (MWA) versus TACE combined with cryoablation (CRA) in treating unresectable HCC. Materials and Methods: From January 2011 to December 2018, 108 patients diagnosed with unresectable HCC were divided into either the TACE-MWA group (n = 48) or TACE-CRA group (n = 60). Overall survival (OS) and time to progression (TTP) were compared between the two groups. To reduce potential bias, a propensity score matching (PSM) was performed. Some complications were observed. Kaplan-Meier survival curves were constructed and compared using the log-rank test. Results: The baseline characteristics of the two groups were balanced. The median OS was 20.9 months (95% CI 14.3-27.6 months) in the TACE-MWA group and 13.0 months (95% CI 8.8-17.1 months) in the TACE-CRA group (P=.096). The median TTP was 8.8 months (95% CI 4.3-13.4 months) in the TACE-MWA group and 9.3 months (95% CI 7.1-11.5 months) in the TACE-CRA group (P =.675). After PSM, 48 patients remained in each group. The median OS in the TACE-MWA and TACE-CRA groups was 20.9 months (95% CI 14.3-27.6 months), and 13.5 months (95% CI 8.4-18.6 months, P = .100), respectively. The median TTP in the TACE-MWA and TACE-CRA groups was 8.8 months (95% CI 4.3-13.4 months), and 8.6 months (95% CI 3.1-14.2 months, P = .909), respectively. The overall incidence rate of ablation-related complications was lower in the TACE-MWA group than in the TACE-CRA group (66.7% vs. 88.3%, P =.006). Multivariate analysis showed that the presence of portal vein tumor thrombus (PVTT) and the maximum diameter of intrahepatic tumor were significant prognostic factors for OS and TTP. Conclusion: The efficacy of TACE-MWA and TACE-CRA in the treatment of unresectable HCC was comparable. TACE-MWA was more promising because of a lower complication rate, especially with regard to thrombocytopenia. Further prospective randomized controlled trials are required to validate our findings.